A mediated–moderated model for green human resource management: An employee perspective - Ren, Zhengyu; Hussain, Rana Yassir (Frontiers in Environmental Science, 2022)
In general, all types and sizes of organizations are responsible for the degradation of the environment. However, manufacturing companies are considered one of the most significant sources of environmental pollution and are pressured to adopt practices to mitigate environmental degradation. Therefore, this research explores the direct and indirect effect of green human resource management (GHRM) on the Chinese manufacturing firm’s environmental performance. To this end, we share a closed-ended questionnaire via a web-based survey to collect data from 306 employees. Data analysis was performed using partial least square structural equation modeling techniques (i.e., PLS algorithm, bootstrapping, and blindfolding). Our research finds a positive and significant effect of GHRM on employee and firm environmental performance. In addition, this research evidenced a partial mediation of employee environmental performance. Besides, our study evidenced that the effect of GHRM on employee environmental performance will be more substantial when there is more involvement of employees’ environmental orientation. This study suggests that manufacturing companies must incorporate GHRM practices, promote green behaviors, respect individual environmental values, and encourage employees to implement those practices for the betterment of firms and the natural environment.